The love for three oranges opera : Aix-en-Provence Festival - Prokofiev, Sergey 1891-1953 (Bel Air Media, 2004)
A fairytale-like production of Prokofiev's The Love for Three Oranges, conducted by Tugan Sokhiev and directed by Philippe Calvario, at the Aix-en-Provence Festival in 2004. After his successful visit in the United States in 1918, Prokofiev received a commission to compose an opera from the director of the Chicago Opera Association, Cleofonte Campanini. The result of this commission was The Love for Three Oranges, a satirical opera drawing its inspiration from Carlo Gozzi's play published in 1761. It is thanks to the avant-garde stage director, Vsevolod Meyerhold, that Prokofiev discovered Gozzi's work. Inspired by this play in which many plots are intertwined, several fairy characters appear, having all the 'Commedia dell'Arte's' features, Prokofiev composed a spirited musical accompaniment on a libretto written by himself in Russian. The premiere took place at the Lyric Opera of Chicago, Illinois, on the 30th of December 1921, in French.
Keywords: Operas; Internet videos